Sexual offending in Asia: a psycho-criminological perspective - Chan, Heng Choon (Psycho-criminology of crime, mental health, and the law, 2023)
Cover -- Title Page -- Copyright Page -- Contents -- List of Figures -- Foreword -- Series Preface -- Acknowledgments -- Endorsements -- About the Author -- Chapter 1 Introduction: Distinguishing Nonhomicidal from Homicidal Sexual Offending -- Introduction -- The Structure of the Book -- Understanding Sexual Offending: Prevalence and Nature -- Nonhomicidal and Homicidal Sexual Offending: Similarities and Differences -- Offenders' Age and Racial Background -- Offenders' Intelligence, Educational Background, and Criminal History -- Offenders' Childhood and Adolescent Development -- Offenders' Behavioral Problems and Psychiatric Diagnoses -- Offenders' Relationship Status at the Time of the Offense -- Offenders' Sexual Deviation -- Offenders' Pre-Crime Characteristics -- Offenders' Crime Scene Characteristics -- Victims' Characteristics -- Conclusion -- References -- Part 1 Theories of Sexual Offending -- Chapter 2 Theories of Sexual Offending: Level I (Multi-Factorial) Theories -- Introduction -- The Precondition Model (Finkelhor, 1984) -- The Integrated Theory (Marshall &amp -- Barbaree, 1990) -- The Quadripartite Model (Hall &amp -- Hirschman, 1992) -- The Confluence Model (Malamuth, 1996) -- The Sexual Promiscuity (SP -- or Impersonal Sex) Pathway -- The Hostile Masculinity (HM) Pathway -- The Evolutionary Theory of Rape (Thornhill &amp -- Palmer, 2000) -- A Theory of Mind Perspective (Ward et al., 2000) -- The Pathway Model (Ward &amp -- Siegert, 2002) -- The Motivation-Facilitation Model of Sexual Offending (Seto, 2019) -- Motivation -- Facilitation -- Situational Factors -- References -- Chapter 3 Theories of Sexual Offending: Level II (Single Factor) Theories -- Introduction -- The Sexual Deviation Theory (McGuire et al., 1965) -- The Cognitive Distortion Theory (Abel et al., 1984) -- The Intimacy Deficits Theory (Marshall, 1989).